Customary Sanctions for the Cancellation of a Marriage Proposal in Krueng Barona Jaya Subdistrict, Aceh Besar: An Examination from the Perspective of Mashlahah - Anas Burhanuddin; Ghufran Jauhar (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
A marriage proposal, or 'meminang' in Indonesian, is a promise a man makes to marry a woman he proposes to. This promise is subject to cancellation due to various factors, either from the man or the woman. However, according to the prevailing customs in Aceh, Indonesia, when a marriage proposal is canceled, the party responsible for the cancellation is subjected to customary sanctions. This research explores the forms of customary sanctions imposed for the cancellation of marriage proposals and examines their compatibility with the concept of 'Mashlahah Mursalah' (public interest). This study employs a qualitative method with an empirical juridical approach. The findings reveal that customary sanctions for canceling a marriage proposal involve the forfeiture of the gold given as a symbol of the bond if the man initiates the cancellation. On the other hand, if the cancellation is initiated by the woman, the gold must be returned twofold. The 'pinangan' gift is considered a non-refundable grant in case of cancellation, regardless of whether the man or the woman initiates it. However, when evaluating the customary sanctions for canceling marriage proposals in light of Mashlahah Mursalah, they are deemed invalid as they contravene several principles of Mashlahah Mursalah, including conflict with the consensus of scholars regarding the law of dowry, contradicting the evidence from the Quran and Sunnah regarding the prohibition of unlawfully taking others' property, and negating greater public interest while opening the door to potential harm.